STRATEGI KOMUNIKASI PT. BANK RIAU KEPRI CABANG SYARIAH PEKANBARU DALAM MEMPROMOSIKAN TABUNGAN SIMPANAN PELAJAR (SimPel iB) - Rezky Widya Utari; Nurjanah " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Competition on banking world necessitated banks to be more active on recruiting customer. On 2015 PT. Bank Riau Kepri Syariah launched student fund saving (SimPel iB) that promoted by visiting schools directly. PT. Bank Riau Kepri Syariah is the first Local Development Bank in Sumatera who launched student fund saving program. This kind of saving has unique concept that named mudharabah, it gives more benefit for student. This kind of saving’s feature also gives dispensation and ease for student.This research aims to find out communicator strategy, audience strategy, message strategy and media tha be used by PT. Bank Riau Kepri Branch Syari’ah Pekanbaru on promoting student fund saving.This research using qualitative research method with descriptive approach and supported with Harold D. Laswell communication theory. The subject of this research was choosing by purposive technique who consists of Chairman, Chief of customer service unit, customer service and teller of PT. Bank Riau Kepri Branch Syari’ah Pekanbaru, 3 teachers and 3 sudents. Data was collected through observation, interview and documentation. Data was analyst using Interactive model of Miles & Huberman. Meanwhile the validity data technique includes extension of participation, triangulation and adequacy of reference.The results of this research showed first, communicator strategy is assignment of employee from customer service unit (customer service, teller, and funding officer) as spokesperson on promoting student fund saving at schools. Second, audience strategy is assignment of islamic school students as main target from the promotion of student fund saving. Third, message strategy is arranging the messege’s content that consists of details about student fund saving, and aslo there is conditioning of messages delivery toward students. Fourth, the using of media on student fund saving promotion is advertising on mass media, print and electronic (newspaper, brochure, television, radio website), and aslo there is outdoor advertising (videotron, bus and bus shelter of Transmetro Pekanbaru, and billboard).Key Words: Communication Strategy, Promotion, Harold D. Laswell Communication Theory